ESTRTOGENE AT EARLY PREGNANCY WITH HERPES-VIRUS EXACERBATION - I. V. Dovzhikova (Scientific Сentre for Family Health and Human Reproduction Problems, 2012)
Decrease of estriol and estradiol concentration, was found, at herpes-viral infection exacerbation, in placenta of pregnant at early stages of gestations. Revealed, change was shown by result of defect of base steroid. — cholesterol content, as well as distribution, of the steroid, hormone syntheses process: low activity of placental 17β-hydroxysteroid dehydrogenase and. inadequacy steroidogenesis regulating mechanism..